A Review of Fiqh Siyasah Dusturiyah on the Phenomenon of Money Politics in the 2023 Village Head Elections in Medan, North Sumatra (Case Study of Medan Estate VIII Veteran Complex) - Rangkuti, Taufik Hidayat; Batubara, Putri Eka Ramadhani (IHSA Institute, 2025)
The election of a village head is a manifestation of popular sovereignty at the village level, aiming to produce leaders who are just, have integrity, and prioritize the interests and welfare of the community. However, in practice, village head elections are often tainted by campaign violations, especially money politics. This phenomenon undermines democratic values, as people's votes can be bought, thus compromising the legitimacy of leadership. This study highlights the 2023 village head election in Medan Estate VIII, Percut Sei Tuan District, Deli Serdang Regency, where strong indications of money politics were found, including cash handouts, basic goods distribution, and promises of projects or positions. The research is analyzed through the perspective of Fiqh Siyasah Dusturiyah, which views leadership as a trust (amanah) and strictly prohibits risywah (bribery), as it contradicts the principles of justice and public interest. In Indonesia's positive law, money politics is considered a criminal act as regulated in various legal instruments such as Law No. 7 of 2017, Law no. 6 of 2014 on Villages, and Government Regulation no. 11 of 2019. This study aims to contribute both academically and practically in building a clean and fair electoral system aligned with Islamic principles, while also raising public awareness of the dangers of transactional politics.